Analysis of compliant mechanisms with lumped compliance - Ong, Lay Yoong. (2008)
Compliant mechanism is a new concept in Precision Engineering that is growing ever more popular due to the unique advantages that it possesses. However, there is no systematic and established synthesis methodology available for the designing of compliant mechanisms. In this study, a simplified analysis method, known as the Linear scheme, for determining the displacement characteristics of a compliant mechanism was introduced. It was found that the linear scheme results when compared to those obtained from the finite element analysis using ANSYS show a maximum difference of 2% only while the time spent on the analysis by the linear scheme was significantly reduced.